PINPOINTING SEMANTIC SHIFTS IN THREE DIVERSE GENERATIONS OF KUNINGAN REGION - Marwito Wihadi; Shely Fauziah (English Journal Literacy Utama, 2019)
Lexical semantic changes were pinpointed on three distinct generations of Kuningan Region so as to find out their tapestry and figure out their prevalent influential factors. They were both analyzed and identified by the employment of the qualitative descriptive method with questionnaires and interview as data collection techniques. It was shown that referring to 141 appearances, broadening and narrowing meaning took up respectively 24.82% and 7.09%. Meanwhile, both Ameliorization and Pejorization made up 29.07%, while Taboo comprised 9.92%. Subsequently, it was notified that all factors were of prevalence, namely linguistic,historical,psychological,social causes, foreign language influences, and novel word needs. It is concluded that typical types of lexical semantic changes as well as their determining factors are prevalently identified. It is imperative that corpus study be implemented and timelines related- lexical semantic changes be touched upon for the further research.